Study on internet addition status of students and its related factors at a medical college in Central Vietnam - Pham, Thi Thien Thanh; Dang, Thi Anh Thu (Tạp chí Y Dược Huế, 2025)
Background: The internet has become an indispensable part of daily life. However, excessive use of the internet can lead to internet addiction, a recognized mental health condition included in the International Classification of Diseases-11 Revision (ICD-11). During the COVID-19 pandemic, this issue appears to have worsened due to increased internet use. This study aimed to determine the prevalence of internet addiction among students at Dang Thuy Tram Medical College in Quang Ngai Province in 2020 and to explore the associated factors. Materials and methods: A cross-sectional study was conducted among 425 full-time students at Dang Thuy Tram Medical College in Quang Ngai Province, Vietnam, in 2020, using a self- administrative questionnaire. Data were collected on demographic characteristics, mental health status and internet use behaviors. The 20-item Internet Addiction Test (IAT-20) was used to assess internet addiction. Statistic analyses including Chi-square tests and multivariate logistic regression to explore factors related to students’ internet addition. Results: The prevalence of medical college students showing mild internet addiction or more severe conditions was 348 among them, 79.9% had mild internet addiction, 19.8% showed internet addiction and 0.3% had a severe condition. Regression analysis indicated that internet addiction was significantly associated with school year (aOR = 2.39, 95%CI:1.08 - 5.29, 2nd year vs 1st year), living arrangement (aOR = 4.15, 95%CI:1.59 - 10.79, living with friends vs living with family), warnings from academic advisors about internet use (aOR = 1.7, 95%CI:1.5 - 6.9), and the time spent for the main purpose of internet use. Conclusion: Internet addiction is highly prevalent among medical college students, especially during the pandemic period. Efforts should be made to raise awareness among student, families, and academic institutions about the risks of internet addiction and promote healthier internet use behaviors.